Janus kinase inhibitors in atopic dermatitis: an umbrella review of meta-analyses - He, Qingying; Xie, Xin; Chen, Qian; Li, Wenquan; Song, Zongzhou; Wang, Xurui; Ma, Xiao; Zeng, Jinhao; Guo, Jing (Frontiers in Immunology, 2024)
Background: Clinicians and healthcare policy makers were drenched with a deluge of overlapping meta-analyses (MAs), and the necessity for comprehensive and clearly defined evidence of Janus kinase inhibitors (JKIs) in atopic dermatitis (AD) is urgent. Methods: Six databases were searched for MAs published until October 2023. Qualitative description of MAs was mainly used, IGA response, EASI75, NRS and adverse effects were cited to describe the efficacy and safety of JKIs. The methodological quality of the included MAs was assessed by the AMSTAR-2, the quality of evidence was evaluated by the GRADE. Results: Sixteen MAs were pooled in this review, five studies appraised JKIs, five were systemic JKIs, five papers assessed abrocitinib only and one was baricitinib. Two studies were “high” methodological quality, 14 MAs were “moderate” quality. 11 MAs integrated the results of JKIs and reported that JKIs provide faster onset of IGA response (RR=2.83, 95% CI [2.25, 3.56], high-quality evidence). Similarly, 10 MAs showed that JAK inhibitors were more effective in reaching EASI75 (RR=2.84, 95% CI [2.2, 3.67], high-quality evidence). Result from 12 MAs showed JKIs were active in reducing PP-NRS (SMD=-0.49, 95% CI [-0.67, -0.32]). All MAs affirmed JKIs added no AEs leading to discontinuation and serious adverse events (P0.05). However, 200mg of abrocitinib had a higher risk on acne (RR=4.34, 95% CI [1.61, 11.71), herpes zoster (RR=1.64, 95% CI [0.42, 6.39]), headache (RR=1.76, 95% CI [1.03, 3]) and nausea (RR=7.81, 95% CI [3.84, 15.87]). Upadacitinib was known to increase acne (RR=6.23, 95% CI [4.08, 9.49]), nasopharyngitis (RR=1.36, 95% CI [1.03, 1.8]) and blood CPK (RR=2.41, 95% CI [1.47, 3.95]). Baricitinib with 2mg associated with blood creatine phosphokinase increased (RR=2.25, 95% CI [1.1, 2.97]). Conclusion: Compared to placebo or dupilumab, the administration of JKIs can more effectively on IGA response, EASI75 and relieved pruritus without severe adverse effect, while accompanied by more acne, nasopharyngitis, headache, and digestive disturbances. The curative effect of 200 mg of abrocitinib is significant and more caution should be given in patients with gastrointestinal dysfunction, acne prone and herpes zoster. Baricitinib and upadacitinib should be avoided in populations at high risk for cardiovascular events.